Utilization of primary eye health services by people from a rural community of Nepal - Gnyawali, S; Bhattarai, D; Upadhyay, MP (Nepalese Journal of Ophthalmology, 2012)
Introduction: Preventable and treatable eye diseases are still major causes of blindness in rural communities. Objective: To find the factors influencing utilization of primary eye health services among the people in a rural community of Nepal. Materials and methods: This was a population-based study with a cross-sectional and descriptive design. Lete Ilaka in Mustang District of Nepal was the study site. Data of knowledge on eye diseases, availability of services and utilization of available services were obtained from female care takers. Association among variables was observed by bivariate analysis. Results: A total of 216 female care takers participated in the study. The median age of the respondents was 39 years. Almost 80 % of the respondents had agriculture as their major occupation and more than a quarter were from lower castes (dalit) community. Low level of educational attainment (OR = 3.1, 95 % CI = 1.6-6.1) and poverty (OR = 2.0, 95 % CI = 1.13-3.43) among respondents were found to be significantly associated with a low level of awareness on eye diseases. The risk of not knowing about eye diseases increased more than 3.5 times when people were illiterate. Locally available eye health services and skills amongst the health workers were found inadequate. Conclusion: Low level of education, poor knowledge of eye diseases and great distance from home to health facilities were found to be factors on the demand side while inadequacy of eye health services and perceived inadequate skills among health workers were identified as factors in the supply side affecting utilization of eye health services among people of Mustang District. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5859 NEPJOPH 2012; 4(1): 96-101